2019 HRS/EHRA/APHRS/LAHRS expert consensus statement on catheter ablation of ventricular arrhythmias. Issue 3 (10th May 2019) - Cronin, Edmond M.; Bogun, Frank M.; Maury, Philippe; Peichl, Petr; Chen, Minglong; Namboodiri, Narayanan; Aguinaga, Luis; Leite, Luiz Roberto; Al‐Khatib, Sana M.; Anter, Elad; Berruezo, Antonio; Callans, David J.; et al.
Abstract: Ventricular arrhythmias are an important cause of morbidity and mortality and come in a variety of forms, from single premature ventricular complexes to sustained ventricular tachycardia and fibrillation. Rapid developments have taken place over the past decade in our understanding of these arrhythmias and in our ability to diagnose and treat them. The field of catheter ablation has progressed with the development of new methods and tools, and with the publication of large clinical trials. Therefore, global cardiac electrophysiology professional societies undertook to outline recommendations and best practices for these procedures in a document that will update and replace the 2009 EHRA/HRS Expert Consensus on Catheter Ablation of Ventricular Arrhythmias . An expert writing group, after reviewing and discussing the literature, including a systematic review and meta‐analysis published in conjunction with this document, and drawing on their own experience, drafted and voted on recommendations and summarized current knowledge and practice in the field. Each recommendation is presented in knowledge byte format and is accompanied by supportive text and references. Further sections provide a practical synopsis of the various techniques and of the specific ventricular arrhythmia sites and substrates encountered in the electrophysiology lab. The purpose of this document is to help electrophysiologists around the world to appropriately select patients for catheter ablation, to perform procedures in a safe and efficacious manner, and to provide follow‐up and adjunctive care in order to obtain the best possible outcomes for patients with ventricular arrhythmias.